The Influence of Motivation and Discipline on the Performance of Nagari Officials: (Study at the Wali Nagari Office of Pasir Talang Barat, Sungai Pagu District, South Solok Regency) - Yesi Elmita; Novera Wandra; O.P. Bismark; Eva Suryani; Mandra Adrika Putra (CV. Strata Persada Academia, 2023)
The background of this research is the lack of discipline and motivation of the Nagari apparatus in work activities at the Wali Nagari Pasir Talang Barat Office. The method used in this study is the Quantitative Descriptive Method. which data is obtained from distributing questionnaires or questionnaires to respondents. The respondents were village officials and institutions within the Wali Nagari Pasir Talang Barat Office. The total was 40 respondents. Data analysis used Multiple Regression Analysis with the SPSS for Windows 25 computer program. From the results of the Motivational TCR, an average score of 4.24 was obtained with a respondent achievement level of 84.83% which was in the good category and the results showed that the research t was 7.071 > t table was 2.024, meaning there is a significant influence between the motivation variable and the performance of the nagari apparatus. Discipline TCR results obtained an average score of 3.49 with a respondent achievement rate of 72.4% which is in the fairly good category, and the results show that the research t is 1.853 <t table is 2.024, this means that there is no significant effect between discipline and the performance of the apparatus and the result of the joint effect of Motivation and Discipline on the Performance of the nagari apparatus is the research F number of 25.955 > F table of 3.25, meaning that there is a significant influence between the variables motivation and discipline with the performance of the nagari apparatus. So it is very important for the Nagari Pasir Talang Barat Government to focus on improving the work discipline of the nagari apparatus.